2009
DOI: 10.1242/dev.034322
|View full text |Cite
|
Sign up to set email alerts
|

Neuropilin-mediated neural crest cell guidance is essential to organise sensory neurons into segmented dorsal root ganglia

Abstract: The peripheral nervous system (PNS) of higher vertebrates is segmented to align the spinal nerve roots with the vertebrae. This copatterning is set up during embryogenesis, when vertebrae develop from the sclerotome layer of the metameric somites, and PNS neurons and glia differentiate from neural crest cells (NCCs) that preferentially migrate into the anterior sclerotome halves. Previous analyses of mice deficient in the class 3 semaphorin (SEMA3) receptors neuropilin (NRP) 1 or 2 raised the possibility that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
62
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 59 publications
(63 citation statements)
references
References 21 publications
(30 reference statements)
1
62
0
Order By: Relevance
“…10,14,18,[34][35][36] We have shown here that NRP1 expression by neural progenitors and macrophages is not required for brain angiogenesis, even though these cell types interact with angiogenic endothelium and can therefore present NRP1 in trans (Figures 1, 3, and 4). It is therefore likely that the ability of NRP1 to interact heterotypically with VEGFR2 in tissue culture models 9 and homophilically in biochemical assays 37 is not important for physiological angiogenesis, at least during brain vascular development.…”
Section: Discussionmentioning
confidence: 80%
“…10,14,18,[34][35][36] We have shown here that NRP1 expression by neural progenitors and macrophages is not required for brain angiogenesis, even though these cell types interact with angiogenic endothelium and can therefore present NRP1 in trans (Figures 1, 3, and 4). It is therefore likely that the ability of NRP1 to interact heterotypically with VEGFR2 in tissue culture models 9 and homophilically in biochemical assays 37 is not important for physiological angiogenesis, at least during brain vascular development.…”
Section: Discussionmentioning
confidence: 80%
“…In addition, it has been reported that the a1 domain of Nrps binds to the sema domain of Sema3 at low [65] or high affinity [68,69], whereas deletion of Nrp1 a1/a2 domains does not affect full-length Sema3A binding [67]. However, the observation that knock-in mice carrying point mutations in the Nrp1 a1 domain display several defective neuronal and non-neuronal phenotypes is consistent with a lack of Sema3A activity [70][71][72][73][74][75][76][77], and clearly indicates that the a1 domain of Nrp1 is required for [193,194] GBM DC101 ↓ Microvessel density, ↑ PVC coverage ↓ basement membrane (↓ collagen IV), ↓ tortuosity and diameter, ↑ oxygenation [195] Fibrosarcoma, squamous carcinoma, NSCLC…”
Section: Sema3 and Their Receptor Complexesmentioning
confidence: 77%
“…Protocols to derive neural crest cells from hPSCs are available (Lee et al, 2007;Menendez et al, 2011), but they produce migratory neural crest cells [marked by the expression of p75 (also known as NGFR) and HNK1 (also known as CD57 and B3GAT1)]. Both premigratory and migratory neural crest cells are able to generate neuronal and non-neuronal descendants (Bronner-Fraser and Fraser, 1989;Bronner-Fraser and Fraser, 1988); however, migratory neural crest cells will undergo progressive lineage specification towards terminally differentiated cell types, which might restrict their usefulness for research purposes (Hari et al, 2012;Schwarz et al, 2009). Therefore, premigratory neural crest cells would be ideal for studying the signaling pathways that control the specification of neural crest fate.…”
Section: Introductionmentioning
confidence: 99%